They give evidence: bodies, borders and the disappeared - Perera, Suvendrini (Routledge, 2006)
In this essay I explore certain relations between bodies and borders as threshold spaces marking both separation and connection, and functioning as the bearers of political meanings. My title refers to Dadang Christanto's installation 'They Give Evidence', a series of standing, naked figures, bearing in their outstretched arms the remnants of burnings, drownings, beatings and other mutilations that leave their subjects stripped of any markers of identity. These nameless bodies, an image of contemporary political violence, invite exploration of the relations between the bodies of the dead and the living, between practices of bearing witness and giving evidence. Beginning with the disappeared of the SIEV X sinking, euphemistically referred to in the recent Senate Inquiry as 'A Certain Maritime Incident', this essay examines ways in which nameless bodies of the dead and disappeared are made present in contemporary Australia as evidence, as political bodies